The concept, influence, and mechanism of human work interruptions based on the grounded theory - Pan, Xiao; Zhao, Xiaokang; Shen, Huali (Frontiers in Psychology, 2023)
With the development of mobile communication technology and the transformation of work methods and modes, work interruptions have become ubiquitous challenges for employees in the workplace. Less attention has been paid to work interruptions in China, especially the research on human work interruptions, which is different from virtual work interruptions. The present study carried out an in-depth interview with twenty-nine employees. Based on the grounded theory method, a psychological and behavioral mechanism model of employees facing human work interruptions, namely, the “human work interruptions – cognitive appraisals – affective responses – behavioral changes” model, was constructed. It is found that (1) cognitive appraisals are the causes of different affective responses and behavioral changes of human work interruptions; (2) cognitive appraisals are feedback behaviors that refer to the reappraisals of the effectiveness and appropriateness of individuals’ affective responses and behavioral changes; and (3) personal traits and environmental characteristics at work influence the affective responses and behavioral changes of human work interruptions at the individual and organizational level. The model constructed in this study further extends the interruption theory and provides implications on how to process human work interruptions in human resource management practice.